Evaluation of the Entrepreneurship Themed Pancasila Student Profile Program: Evaluasi Program Profil Siswa Pancasila Bertema Kewirausahaan - Safira, Adhe Okta; Auliya, Vivi Rizky; Fandora, Karmila; Friyatmi; Susanti, Desi (Academia Open, 2025)
General Background: Education in Indonesia is undergoing transformation through the Merdeka Curriculum, which emphasizes strengthening the Pancasila Student Profile (P5) as a foundation for character and competence development. Specific Background: Within this framework, entrepreneurship has been chosen as a theme at SMA Negeri 1 Kapur IX to foster creativity, independence, and collaboration, while preparing students for real-world challenges. Knowledge Gap: Previous studies have generally assessed P5 broadly or with other themes, leaving limited in-depth evaluation of entrepreneurship-focused P5 programs in specific school contexts. Aims: This study aimed to evaluate the implementation of the P5 entrepreneurship program using the CIPP model (Context, Input, Process, Product) to identify strengths, weaknesses, and areas for improvement. Results: Findings indicate that the program aligns with school goals and national policy, supported by adequate resources, effective teaching modules, and student engagement, though challenges persist in teacher readiness, socialization, and sustaining character formation. Novelty: This study provides explicit, context-specific insights into P5 entrepreneurship, offering practical evidence distinct from broader analyses. Implications: The results inform schools and policymakers to refine P5 implementation, strengthen teacher training, and enhance collaboration with entrepreneurial practitioners to cultivate resilient, innovative learners. Highlight : P5 program evaluated using CIPP model covering context, input, process, product. Implementation supports student readiness, facilities, and entrepreneurship modules. Results show improved creativity, independence, and cooperation among students. Keywords : P5, Entrepreneurship, CIPP Evaluation, Student Profile, Character Building